Role of civil society organizations in achieving community impact - Chai, Zheng; Chai, Stefanie (The University of Edinburgh, 2022)
This three-paper dissertation advances theoretical and empirical understandings of how internal, external, and societal systems of civil society organizations (CSOs hereafter) governance influence the achievement of community impact. It therefore aims to provide an understanding of how various CSO governance systems generate community impacts in different ways. The first paper considers the internal governance of CSOs by focusing on governance structure and processes. The second paper examines the external governance of CSOs by focusing on their adaptation to unexpected external events. Finally, the third paper investigates societal governance by focusing on the mechanisms and design principles of governing the commons. The dissertation considers qualitative case studies based in Edinburgh, Scotland – a city that has been greatly influenced by the civil-society movement. The three papers that make up the dissertation are presented in chapters four, five, and six. Paper one explores the role of organizations in the process of internal governance of community-based public spaces. Through an analysis of four CSOs, this study finds that the decision-making process, governance structures, and multi-stakeholder activities are crucial determinants of the efficacy with which the organizational mission is maintained through internal governance. Paper two explores how CSOs developed emergency operations during the first Covid-19 lockdown of 2020 to further develop the understanding of adaptation by organizations facing an exogenous shock. This paper contributes to the understanding of crisis management and resilience through a model that conceptualizes: the overall adaptation processes, identifies specific variants to this process, and reveals the mechanisms by which this learning informs adaptation to organizational structure. Paper three aims to investigate societal governance by focusing on the mechanisms and design principles of governing the commons, which gains further insight into the mechanisms and processes related to governance structure and ownership, and the role they play in supporting the community interactions that build civil society. The presented case studies – four community-based public spaces managed by CSOs – reveal four mechanisms that resonate with different configurations of Ostrom’s design principles, which they use to successfully govern the spaces.
The Role of Civil Society Organizations in Achieving Community Impact
Keywords: civil society organizations; CSO; community interactions; societal governance; civil society